How does green innovation strategy influence corporate financing? corporate social responsibility and gender diversity play a moderating role - Javeed, Sohail Ahmad; Teh, Boon Heng; Ong, Tze San; Chong, Lee Lee; Abd Rahim, Mohd Fairuz; Latief, Rashid (Multidisciplinary Digital Publishing Institute, 2022)
Global warming is becoming more and more of a concern, leading authorities to take action. The industrial sector is a key contributor to environmental and social problems. Based on stakeholder theory and agency theory, this research proposes that green innovation strategies at the firm level can overcome the industry’s negative environmental impact. As a result, the focus of this research is on green innovation strategies for corporate financing. In addition, this research suggests that corporate social responsibility and gender diversity directly affect corporate financing and their interaction. This study used Chinese 301 manufacturing firms (3010 observations) for the period 2010–2019 for this purpose. This study looks into panel data issues in depth by using approaches such as the fixed effect and generalized method of moment. The feasible generalized least square was employed to increase robustness. Furthermore, green innovation strategies were used for corporate financing. Second, the study discovered that corporate social responsibility aided firm financing. Our findings also imply that corporate social responsibility helps to attenuate the association amid green innovative strategies and corporate financing. Finally, these findings revealed that gender diversity had a favorable effect on corporate financing. Furthermore, this study confirmed that the moderating role of gender diversity is beneficial to green innovative strategies and corporate financing. These findings add to the literature by providing policymakers and regulatory bodies with useful information for advancing sustainable development.